Granular cell tumor of the breast mimicking malignancy: a case report with a literature review. (December 2018) - Fujiwara, Keishi; Maeda, Ichiro; Mimura, Hidefumi
Granular cell tumor (GCT) is a rare neoplasm of the soft tissues and <1% of all GCTs are malignant. Initially, GCT was considered a myogenic lesion affecting the female breast (myoblastoma). We report the case of an 83-year-old woman with a palpable lump in the left breast; mammography and ultrasound showed an irregular lesion. It was difficult to differentiate it from a malignant lesion; therefore, we performed core needle biopsy and histopathologic examination and immunohistochemical studies revealed a GCT of the breast.